College Adjustment of Football Players: Predictors of First Semester Adjust to College among NCAA Division III Intercollegiate Football Players - Quarforth, Scott C.; Brewer, Britton W.; Petitpas, Albert J.; Champagne, Delight E.; Cornelius, Allen E. (My University, 2003)
This study examined predictors of first-semester adjustment to college among 48 first-year intercollegiate football players. Participants completed measures oflife stress, social support, quality of their relationship with parents, quality of their roommate relationship, sport satisfaction, athletic identity, and adjustment to college near the end of the first semester. The predictor variables accounted for 43% of the variance in adjustment to college, with quality of the roommate relationship and sport satisfaction emerging as significant (p < .05) predictors of adjustment. The results highlight the role of social and sport-related factors in how well first-year intercollegiate football players adjust to college. Recommendations for facilitating positive adjustment were provided. The more favorably participants perceived the relationship with their roommates and the more satisfied they were with their involvement in football, the better their adjustment near the end of the first semester of college. Contrary to the hypothesized pattern of results, however, factors found previously to relate to adjustment to college in the general student body (i.e., life stress, social support, and relationship with parents) were not associated with the football players' adjustment to college. Social support did not moderate the relationship between life stress and adjustment, and athletic identity did not moderate the relationship between sport satisfaction and adjustment. The failure of life stress, social support, and parent relationship to predict adjustment to college among first-year intercollegiate football players is surprising in light of research documenting associations between these variables and adjustment to college for the general student population (Compas et al., 1986; Holmbeck & Wandrei,1993; Prancer et al., 2000; Pratt et al., 2000; Wintre & Yaffe, 2000).
Keywords: transitions; freshmen; football; Division III; stress